The forgotten ocean: Why COP26 must call for vastly greater ambition and urgency to address ocean change - Laffoley, D; Baxter, JM; Amon, DJ; Claudet, J; Downs, CA; Earle, SA; Gjerde, KM; Hall-Spencer, JM; Koldewey, HJ; Levin, LA; Reid, CP; Roberts, CM; et al. (Wiley, 2021)
1. Of all the interconnected threats facing the planet, the top two are the climate and the biodiversity crises. Neither problem will be solved if we ignore the ocean. To turn the tide in favour of humanity and a habitable planet, we need to recognize and better value the fundamental role that the ocean plays in the earth system, and prioritize the urgent action needed to heal and protect the ocean at the ‘Earthscape’ level – the planetary scale at which processes to support life operate.